2019
DOI: 10.1007/s00268-019-04985-1
|View full text |Cite
|
Sign up to set email alerts
|

The Operative Output of District Hospitals in KwaZulu‐Natal Province is Heavily Skewed Toward Obstetrical Care

Abstract: Introduction District hospitals are key to providing universal coverage of essential surgery and for strengthening surgical care in general. This audit set out to quantify the surgical output of all the district hospitals in KwaZulu-Natal Province (KZN) over a 6-month period to see whether district hospitals were delivering the surgical care they are expected to deliver. Results There were a total of 18,871 operations performed at 37 district hospitals in KwaZulu-Natal from July to December 2015. The number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 13 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…We have previously shown that the district hospitals of KZN perform CSs, but deliver the other two bellwether procedures to a very limited extent. [6] In that study, we found that a total of 18 871 operations were performed at 37 district hospitals in KZN from July to December 2015. [6] Of the bellwether procedures performed at these institutions, 96.1% were CSs, 2.1% were laparotomies and 1.8% were ORFs.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…We have previously shown that the district hospitals of KZN perform CSs, but deliver the other two bellwether procedures to a very limited extent. [6] In that study, we found that a total of 18 871 operations were performed at 37 district hospitals in KZN from July to December 2015. [6] Of the bellwether procedures performed at these institutions, 96.1% were CSs, 2.1% were laparotomies and 1.8% were ORFs.…”
Section: Resultsmentioning
confidence: 93%
“…[6] In that study, we found that a total of 18 871 operations were performed at 37 district hospitals in KZN from July to December 2015. [6] Of the bellwether procedures performed at these institutions, 96.1% were CSs, 2.1% were laparotomies and 1.8% were ORFs. For almost all these district hospitals, the percentage of laparotomies and ORFs performed was small to negligible, while the percentage of CSs was high.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…In South Africa, most soft tissue sepsis should be managed at the clinic or district hospital level [4,5]. Previous work has, however, suggested that the district surgical system in KZN is not functioning appropriately [10][11][12][13]. The district institutions do not seem to be delivering the so-called Bellwether procedures (laparotomy and ORIF) in a meaningful capacity, and there is evidence that rural patients with acute appendicitis who present to district hospitals have worse outcomes than those who present directly to higher levels of care [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%